Field study on thermal environment and thermal adaptability of classrooms in Hefei area universities. Issue 1 (June 2021) - Li, Wei; Fu, Kousuo; Shui, Taotao; Gao, Guotai; Yin, Linjian; Wan, Xiaokang; Lv, Kefeng
Abstract: In order to study the thermal environment and thermal comfort of university classrooms, a long-term on-site study of a university classroom in the Hefei area is carried out by combining questionnaires and on-site data collection. A thermal sensory model applicable to the university classroom in the Hefei area is established, and through analysis it is found that the measured thermal neutral temperature is lower than the predicted thermal neutral temperature under the PMV model, and the corresponding 90% acceptable temperature ranges under the measured and PMV models are 22.0~25.6°C and 17.2-24.9°C respectively. Opening and closing doors and windows and adding and removing clothing are the preferred thermal adaptive behaviors of the subjects when the indoor thermal environment changes.